Hubungan Tingkat Pendikan Pasien Tuberkulosis terhadap Kejadian Multidrug Resistant Tuberkulosis di Kota Surakarta - Vera Vera (Lembaga Pengembangan Kinerja Dosen, 2024)
This study aims to analyze the relationship between the educational level of tuberculosis (TB) patients and the incidence of Multidrug Resistant Tuberculosis (MDR-TB) in Surakarta City. The study utilized an observational analytic design with a case-control approach, involving 304 subjects, consisting of 76 MDR-TB patients and 228 non-MDR TB patients. Data were collected through surveys, and the analysis was conducted using the chi-square test. The results showed that a low educational level was significantly associated with an increased risk of MDR-TB (OR=3.26; 95% CI=1.88-5.66; p<0.001). Patients with a lower educational level were 3.26 times more likely to develop MDR-TB compared to those with higher education. This study concludes that educational level plays a crucial role in the incidence of MDR-TB and emphasizes the need for improved health education programs to enhance treatment adherence and prevent drug resistance among TB patients.